2010
DOI: 10.3346/jkms.2010.25.7.1024
|View full text |Cite
|
Sign up to set email alerts
|

Cox-2 and IL-10 Polymorphisms and Association with Squamous Cell Carcinoma of The Head and Neck in a Korean Sample

Abstract: Cyclooxygenase-2 (COX-2) is involved in inflammation and carcinogenesis. Interleukin-10 (IL-10) is also regarded as anti-inflammatory factors with the multi-functional ability to positively and negatively influence functional immunity and tumor development. Genetic polymorphisms of COX-2 and IL-10 might contribute to the development of squamous cell carcinoma of the head and neck (SCCHN). The purpose of this study was to evaluate the association of COX-2 and IL-10 single nucleotide polymorphisms (SNPs) with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 23 publications
1
14
0
Order By: Relevance
“…Ultimately, nine studies 29 37 38 39 40 41 42 43 44 satisfied the outlined inclusion criteria and characteristics ( Table 1 and Supplemental Table S4 online), including the quality assessment score that was generated based on the Newcastle-Ottawa Scale of studies. Each of the nine studies focused on the association of the −1082A > G polymorphism with HNC risk 29 37 38 39 40 41 42 43 44 , and six studies investigated the association of the −819T > C and −592A > C variants with HNC risk 29 37 39 42 43 44 . Three studies focused on Caucasian populations 29 38 40 , and six studies focused on Asian populations 37 39 41 42 43 44 .…”
Section: Resultsmentioning
confidence: 99%
“…Ultimately, nine studies 29 37 38 39 40 41 42 43 44 satisfied the outlined inclusion criteria and characteristics ( Table 1 and Supplemental Table S4 online), including the quality assessment score that was generated based on the Newcastle-Ottawa Scale of studies. Each of the nine studies focused on the association of the −1082A > G polymorphism with HNC risk 29 37 38 39 40 41 42 43 44 , and six studies investigated the association of the −819T > C and −592A > C variants with HNC risk 29 37 39 42 43 44 . Three studies focused on Caucasian populations 29 38 40 , and six studies focused on Asian populations 37 39 41 42 43 44 .…”
Section: Resultsmentioning
confidence: 99%
“…An association between IL-10 rs1800872 and cervical cancer has been found, and no association with prostate cancer was detected for IL-10 rs1800871 (31,32). Thus far, only one other study has evaluated the association of IL-10 polymorphisms with risk of head and neck cancers in a Korean population, but no association was detected between the three main polymorphisms and the risk of head and neck cancers (33). Several studies have demonstrated that IL-10 polymorphisms are associated with HPV clearance.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to functional SNPs, tag SNPs were selected for the six prostaglandin pathway genes. Data of Han Chinese in Beijing surveyed by the HapMap Project (Jeong et al , ) were downloaded using Haploview (Barrett et al , ), and the Tagger program (de Bakker, ) was used to select tag SNPs for each gene with r 2 set at 0.8. 10‐kb regions upstream and downstream of each gene were included to cover variants in potential regulatory elements.…”
Section: Methodsmentioning
confidence: 99%
“…All of the seven previous studies on the association between genetic polymorphisms of the PG pathway and HNC risk have only included PTGS2 (COX‐2) (Chiang et al , ; Lin et al , ; Peters et al , ; Jeong et al , ; Mittal et al , ; Lakshmi et al , ; Niu et al , ). In the present study, we conducted a comprehensive investigation of genetic polymorphisms of six genes ( PGDS, PTGDS, PTGES, PTGIS, PTGS1, and PTGS2 ) in the PG pathway and examined their association with HNC risk.…”
Section: Introductionmentioning
confidence: 99%